A cultura da terra e a cultura do mar - Lourido, Francisco Calo (PORTVGALIA: Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da Faculdade de Letras da Universidade do Porto, 2018)
Despite the neighbourhood, having a common language and belonging to the same ethnic group, the very different physical environments in which farmers and sailors live and work created two opposing worldviews and two radically different ways of living.